2013
DOI: 10.1097/opx.0b013e31827cda5b
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Daily Light and Ultraviolet Exposure in Young Adults

Abstract: The current literature suggests that there is a link between myopia protection and spending time outdoors in children. Our data provide some evidence of this relationship in young adults and highlight the need for larger studies to further investigate this relationship longitudinally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 29 publications
1
71
0
Order By: Relevance
“…A consistent finding from these studies is that both adults and children spend a relatively small proportion of the day in bright outdoor light conditions (Dharani et al, 2012;Alvarez & Wildsoet, 2013;Schmid et al, 2013;Read et al, 2014Read et al, , 2015. There has however, been some variability between these studies in terms of the average light exposure levels reported and the association between light exposure and refraction.…”
Section: Hypothesismentioning
confidence: 71%
See 4 more Smart Citations
“…A consistent finding from these studies is that both adults and children spend a relatively small proportion of the day in bright outdoor light conditions (Dharani et al, 2012;Alvarez & Wildsoet, 2013;Schmid et al, 2013;Read et al, 2014Read et al, , 2015. There has however, been some variability between these studies in terms of the average light exposure levels reported and the association between light exposure and refraction.…”
Section: Hypothesismentioning
confidence: 71%
“…These potential drawbacks associated with questionnaires have been the catalyst for a number of recent studies that have quantified the light exposure (Backhouse & Phillips, 2011;Dharani et al, 2012;Alvarez & Wildsoet, 2013;Schmid et al, 2013;Read et al, 2014Read et al, , 2015Ostrin, 2017) and/or physical activity (Deere et al, 2009;Guggenheim et al, 2012;Read et al, 2014Read et al, , 2015 using objective techniques such as wearable sensors (Dharani et al, 2012;Alvarez & Wildsoet, 2013).…”
Section: Light Exposure and Human Myopiamentioning
confidence: 99%
See 3 more Smart Citations